Using Arsoy™ as a protein supplement in growing cattle diets - Marston, T.T.; Kreikemeier, K.K.; Wankel, L.E.; Huck, G.L.; Wistuba, T.J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Arsoy™ Soybean Feed is a by-product from the manufacture of soy protein isolate. It contains nearly 30% crude protein, but there is little documentation about its feeding value. Therefore, we fed basal growing diets of corn silage and stover to 196 crossbred heifers and supplemented those diets with soybean meal, Arsoy, or a combination of soybean meal and high moisture corn to determine the feeding value of Arsoy. Our results suggest that Arsoy can be substituted for soybean meal in growing cattle diets, without any negative impact on animal performance, dry matter intake, or feed efficiency.
Keywords: Beef; Protein supplementation; Soybean by-products; Arsoy; Heifers